Health Promotion about Stunting Management Through the Precede - Proceed Model Approach - Andriyani, Septian; Fitriana, Lisna Anisa; Sulastri, Afianti (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2024)
ABSTRACT Stunting is a problem of chronic malnutrition caused by insufficient nutritional intake over a long period of time due to the provision of food that is not in accordance with nutritional needs. Health cadres and mothers who have children under five are community groups who need to be equipped with stunting management including prevention, treatment and stimulation of development in children. The aim of Community Service (PKM) aims to provide health promotion in the form of education and training about stunting management through the Precede-Proceed Model approach. The method for this form of PKM activity is in the form of health promotion, simulation, and training for health cadres and mothers who have children under five in the traditional village of Cireundeu, Cimahi City which is carried out offline. The target audience for this activity is health cadres and mothers who have children under five, totaling 52 people. The results of the activity showed that there was a difference in the average knowledge scores of cadres and mothers with children under five. When the pre-test showed a score of 93 and the post-test showed a score of 98 with an average increase in score of 5 points. Health promotion related to stunting management in the form of prevention and management of stunting is considered effective in increasing the knowledge and skills of mothers with children under five and health cadres. By forming community groups that can prevent stunting, the quality of growth and development in children will be more optimal. Keywords: Health Promotion, Stunting Management, Precede Proceed Model